Pengaruh Special Event Jakarta Sneakers Day Terhadap Citra PT. Infia Pariwara Nusantara : Studi Pada Pengunjung Event Jakarta Sneakers Day 2023 - Ridho Ramadhan; Sa’diyah El Adawiyah (Jurnal Kajian dan Penelitian Umum, 2024)
Events are one of the public relations activities that can be used to promote a company. In Public Relations studies, events are called special events. An event organizer is a type of business in the field of entertainment. An event organizer is tasked with organizing and designing the course of an event. PT Infia Pariwara Nusantara is a company that specializes in event activities. PT Infia Pariwara Nusantara creates its own events such as Jakarta Sneakers Day, Melodi Alam, and Fantoystic World, and also provides event, campaign and production activity services for brands. The Jakarta Sneakers Day event itself has been held by PT Infia Pariwara Nusantara since 2017 and immediately received public attention. The purpose of this research is to find out the Special event Jakarta sneakers day, the image and influence of the Special event Jakarta sneakers day on the image of PT. Infia Pariwara Nusantara. The theories used in this research are Public Relations theory, Marketing Public Relations theory, Event theory, Special Event theory, and Image theory. The conceptual approach used in this research is Lesly's special event concept, namely 5 W + 1 H and is linked to Nimpoeno's image formation theory which explains Perception, Cognition, Motivation and Attitude. This research is quantitative research with a survey method and the data collection technique used is a questionnaire. The population in this study was 34,640 visitors to Jakarta Sneaker Day and the sample used was 100 respondents using the Taro Yamane formula. The sample data collection technique in this research used random sampling. The results of this research show that there is an influence between the Jakarta Sneaker Day Special event on the image of PT. Infia Pariwara Nusantara. This can be seen from the correlation coefficient of 0.650. The magnitude of the influence of the Jakarta Sneaker Day Special event on the image of PT. Infia Pariwara Nusantara is 0.422 or equal to 42.2%. Meanwhile, the remaining 57.8% was influenced by other variables not examined in this research